Pengaruh Kepemimpinan Kepala Sekolah, Profesional Guru dan Motivasi Kerja Terhadap Kreativitas Guru - Lambok Hotmatua Samosir; Emilda Sulasmi; Indra Prasetia (UMSU, 2023)
This study aims to analyze the influence of the principal's leadership, teacher professionalism, work motivation on the creativity of SD Negeri Se District teachers, South Sibolga. The sample of this study was all PNS teachers who had SDN certification in Sibolga Selatan District, totaling 91 people. Methods of data collection using a questionnaire. Then tested the validity and reliability. The data analysis technique used is multiple linear regression, hypothesis testing, and the coefficient of determination. The results of the study show that: (a) The relationship between the principal's leadership variable (X1) and teacher creativity (Y) is in the form of a regression equation Y = 55.438 + 0.315 X1. The R square value is 0.191, meaning that there is an influence of the principal's leadership on teacher creativity of 19.1% (b) The relationship between teacher professional variable (X2) and teacher creativity (Y) is in the form of a regression equation Y = 48.211 + 0.431 X2. R square value of 0.289. there is a teacher professional influence (X2) on teacher creativity of 28.9%, (c) Work Motivation (X3) on teacher creativity (Y) in the form of a regression equation Y = 45.549 + 0.431 X3. R square value of 0.502. This means that there is an influence of Work Motivation (X3) on teacher creativity of 50.2%, (d) Because Fcount Ftable or 46.411 2.710 then Ha is accepted and Ho is rejected. R square value of 0.982. This means that the Principal Leadership (X1), Teacher Professional (X2) and Work Motivation (X3) variables affect Teacher Creativity (Y) together by 19.1% + 28.9% + 50.2% = 98.2%, and the remaining 0.8% is determined by other reasons not examined.